Understanding QR Code Mobile Payment Adoption in Jamaica: A University Community Perspective - Williams, Ray-St. Michael; Facey-Shaw, Lisa; Wade, Tara (LACCEI, 2024)
The rise of mobile payments and digital wallets has revolutionized digital payment methods for businesses and consumers worldwide. This study focuses on Jamaica, a country with 82% internet usage penetration among its population and 103 mobile cellular subscriptions per 100 persons in 2021, surpassing the world average of 63%. Despite these promising figures, the adoption rate of mobile payment solutions remains relatively low. Adopting the Unified Theory of Acceptance and Use of Technology (UTAUT, this study investigates the adoption patterns of mobile payment systems, specifically QR code payments, among 91 participants, predominantly young adults and women, at the University of Technology, Jamaica. Our preliminary findings suggest a growing acceptance of mobile payment technologies among the educated youth, yet highlights a gap between technological accessibility and actual usage. This paper delves into the factors driving and hindering mobile payment adoption, such as public awareness, perceptions of security, technical challenges and perceived utility. It offers valuable insights for policymakers, educators, and financial technology stakeholders. The study offers insights into the challenges and opportunities in promoting digital financial services in developing economies. It also underscores the importance of tailored strategies that address specific barriers to mobile payment adoption, thereby enhancing financial inclusion ...